Socio-Economic Determinants of Changes in the Crime Rate in Ukraine - Oglikh Valentina V.; Volkova Valentina V.; Shapovalov Aleksii V. (Problemi Ekonomiki, 2018)
The aim of the article is to clarify the basic socio-economic determinants of criminal behavior of an individual in the “person-society” system in order to determine directions and prospects for decreasing the crime rate in Ukraine based on the techniques and methods of mathematical modeling. An analytical study of the statistical laws that link human capital and the criminal rate in the country in a regional context as well as the criteria that determine the level and quality of life of the Ukrainian population is extremely important. Such research will contribute to changes in the generally accepted views on this issue in the Ukrainian society, development of modern society, elimination of deformations, as well as formation of awareness of the need to preserve and enhance human resources. The results of the factor, component, cluster analysis and forecasting confirmed that it is the indicators selected in the work that have the most significant influence on the crime rate in the country, and therefore determine the main directions of the corresponding socio-political transformations. The clustering of regions of Ukraine using k-means by minimizing the average intraclass distance has allowed mapping the projected trends in crime rates across regions of Ukraine. The identified in the work characteristics of negative aspects of social reality, which directly or indirectly form a complex of crimes, act within the political, economic, organizational, managerial, social, moral, spiritual, socio-psychological, cultural, and educational spheres of life. The results of the study give every reason to assert that with the constant negative determinants identified, upon the condition that the current socio-economic situation is preserved, there will be no real positive changes in the criminal rate.